TEACHERS’ COMPETENCIES USING VIRTUAL WORKSPACES IN THE NEW NORMAL: A SEQUENTIAL EXPLANATORY STUDY - Gonzaga, Lheane; Andrade, Ina Berenice L.; Ballatan, Arlene A.; Guzman, Jaymee O. De; Valenzuela, Janelle W. (International Interdisciplinary Conference on Sustainable Development Goals, 2024)
This research undertaking aimed to determine the competencies and the experiences of elementary teachers using virtual workspaces in the new normal set-up brought about by Covid-19. The study made use of the sequential explanatory research design with the virtual interview and survey as the main instruments for gathering the relevant needed data. It employed the purposive sampling technique in determining the respondents and participants who actively participated in the virtual survey and interview, respectively. These key informants of the study are the elementary teachers in the District of San Luis, Pampanga who have been utilizing the Google workspaces- sixty (60) teacher- respondents and ten (10) teacher-participants. The results of the study revealed that the elementary teachers were knowledgeable, skillful, and capable of using the virtual workspaces but there was a significant difference with regard to their ages and years of teaching experiences. Likewise, the results indicated that the teachers’ capabilities are important in utilizing the virtual workspaces in enhancing the teaching-learning process and in adapting to the new environment where technology is a must. To enhance the teachers’ competencies in the new normal mode of teaching, these were some of the recommendations offered: teachers who were appropriately screened and whose ages range from 31 and above should be sent to ICT-related seminars and the like, and that they must be continuously provided with full access to Google workspaces even when the face-to-face mode be implemented again.